Improving Students’ Reading Ability by Using Detailed Reading at SMK Wiratama 45.2 Wonosobo - Adnan Firdaus Setyarta; Arif Widyantoro (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2026)
This study aims to improve the reading skills of Class XI APH 1 students at SMK Wiratama 45.2 Wonosobo by applying the Detailed Reading technique. Initial observations revealed that students struggled to understand English texts, had limited vocabulary, and lacked motivation to learn due to monotonous teaching methods. To address these issues, the researcher employed the Classroom Action Research (CAR) approach in two cycles, each comprising planning, action, observation, and reflection stages. Data collection instruments included pre- and post-tests, observations, interviews, and documentation. The results showed significant improvement in students' reading ability after implementing the Detailed Reading technique. The average pre-test score of 57.86 increased to 64.82 in the first post-test cycle and increased again in the second. The Detailed Reading technique was effective in helping students understand text content more deeply, enrich vocabulary, and increase interest in and active participation in English learning. This study concludes that using the Detailed Reading technique can significantly improve students' reading ability and is an effective strategy for teaching English at the vocational high school level.